Muhammad Amin Abdullah's Thought on Multicultural Islamic Education - Azizah Hanum OK (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
In the Era of Disruption 4.0, education should have become one of the media in forming positive attitudes towards various realities. The attitude in question is an attitude of being willing to accept, acknowledge, and respect other people with their respective ethnicities, this is also stated in the slogan